The Effect of E-Payment on Global Consumers: A Systematic Literature Review - Kurniawan, Adiq Riyan; Prasetyo, Dimas Dwi; Indriani, Farida (Research Horizon, 2024)
The development of electronic technology has greatly influenced the paradigm shift in payment transactions, leading to the emergence of a payment method known as Electronic Payment (e-Payment) which is an innovation in payment transactions in this modern era. Strong and widespread connectivity plays an essential role in driving a significant transformation in the financial market and operations. Digitalization and the utilization of the internet have made the global economic system more advanced and practical, thus boosting economic growth. This research aims to examine the implementation of e-payment among consumers globally and its impact on business growth, economic growth, and productivity. This study investigates the key factors influencing patterns and trends in the implementation of e-payments. This research employs a systematic literature review related to implementation of e-payment and its influence on business growth, economic growth, and productivity, including articles published from 2020 to 2024 to ensure relevant findings. The results of this study are expected to confirm the significance of e-payment implementation on business growth, economic growth, and productivity.